The Fulfillment of Post-Divorce Rights for Former Wives and Children in Bantaeng Regency: A Maqāṣid al-Sharī‘ah Analysis - Wahda, Nur Aqiqah; Sabir, Muhammad; Anas, Muh Fauzi (MUI Sulawesi Selatan, 2025)
This study investigates the public understanding and practical realization of post-divorce rights for ex-wives and children in Bantaeng Regency, where 379 divorce cases were recorded in 2022. Despite clear legal provisions, many of these rights remain unfulfilled, reflecting a gap between legal rulings and social implementation. The purpose of this research is to examine how the local community perceives and practices the fulfillment of these rights in light of Maqāṣid al-Sharī‘ah, the higher objectives of Islamic law. This study investigates the public understanding and practical realization of post-divorce rights for ex-wives and children in Bantaeng Regency, where 379 divorce cases were recorded in 2022. Despite clear legal provisions, many of these rights remain unfulfilled, reflecting a gap between legal rulings and social implementation. The purpose of this research is to examine how the local community perceives and practices the fulfillment of these rights in light of Maqāṣid al-Sharī‘ah, the higher objectives of Islamic law. The findings reveal a significant disconnect between legal provisions and societal behavior. Although the Bantaeng Religious Court implements Supreme Court Circular (SEMA) No. 1 of 2017, which mandates the inclusion of post-divorce obligations (e.g., maintenance of iddah, mut'ah, and child support) in court verdicts, enforcement remains weak. When fathers neglect their responsibilities, mothers are often unaware of their right to request legal execution of these obligations. This research contributes original insights into the socio-legal dynamics of post-divorce justice in rural Indonesia. It highlights the need for broader legal literacy and institutional support. The study recommends that legal authorities and local governments actively disseminate information about SEMA No. 1 of 2017 to ensure post-divorce rights are properly understood and enforced.